Investigating the relationship between swing weight and swing speed across different sports using historical data - Schorah, D.; Choppin, S.; James, D. (Procedia Engineering, 2012)
In many sports, the maximum swing speed of a racket, club or bat is a key performance parameter. Previous research has suggested that a logarithmic relationship exists between the resultant swing speed and the swing weight/moment of inertia of the implement. However, these studies have only focussed on one specific sport and relatively little is known about the effect of swing weight on swing speed across the wider spectrum of sport. Data was collated on the swing speeds achieved in numerous sports that employ an implement and a swinging motion. A range of typical swing weights were determined for the various implements and the data normalised to common conventions such that comparisons could be made. This meta-analysis established a new relationship between swing weight and swing acceleration, valid across the wide range of implements considered. This relationship was found to be of the form a=C/Im, where C is a player constant and m=0.59 (p<0.01).